Про дослідження маловідомих наукових праць Якова Пилипа Кулика - Лісковець, С. М. (НТУ "ХПІ", 2011)
Вперше зроблений аналіз маловідомих наукових робіт Якова Пилипа Кулика з теорії алгебраїчних рівнянь, прикладної механіки та аналіз деяких таблиць вченого

An analysis of Jacob Philip Kulik’s little known scientific works on the theory of algebraic equations in Applied Mechanics and an analysis of some scientist’s tables have been for the first time carried out
Keywords: теорія алгебраїчних рівнянь; прикладна механіка; таблиці; вища математика; scientific works; theory of algebraic equations; applied мechanics; scientist’s tables